2017
DOI: 10.5999/aps.2017.44.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fat Grafting as a Last Resort for Unsustainable Pain in a Woman with Multiple Osteochondromas

Abstract: Multiple osteochondromas (MO) is characterized by the formation of osteochondromas throughout the entire body. Although the evidence regarding its pathogenesis is well understood, no curative treatment for the disorder is available. Patients can be treated symptomatically by surgical removal of painful osteochondromas. Unfortunately, some patients still suffer from severe pain, even after surgery. We report on a case concerning a 48-year-old woman with a history of MO who presented with persistent pain after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Various characteristics including tumor size, shape, location, and vascularity can be valuable data at the preoperative stage. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various characteristics including tumor size, shape, location, and vascularity can be valuable data at the preoperative stage. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Various characteristics including tumor size, shape, location, and vascularity can be valuable data at the preoperative stage. 16 Benign cartilaginous tumors mostly have a slowly progressive course and do not show significant symptoms. However, they are occasionally located in the subungual area and are accompanied by toenail deformities.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a bone scan to check for sarcomatous change is recommended at least once after entering puberty. It also needs to be noted that the topics of orphan drugs and next-generation pain control for MO have been underinvestigated (Beltrami et al, 2016;Karibe, Fukui, Sekikawa, Shiratori, & Fujimori, 2008;Negenborn, Moerman, & Ham, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…14 PFG has been successfully implemented as treatment for a number of pedal conditions such as diabetic foot ulcers, pedal fat pad atrophy, thromboangiitis obliterans, plantar fibromatosis, and plantar osteochondromas. 4,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Although it has be shown that grafted lipoaspirate redistributes over time in the plantar foot surface, it retains its supportive and analgesic function. 22 Considering this, the investigators expected that PFG holds potential therapeutic benefit to treat conditions, which results in elevated localized pedal pressure by providing a mechanism to dissipate said elevated pressure.…”
Section: Introductionmentioning
confidence: 99%